Simulation of high-efficiency CdTe solar cells with Zn1-xMgxO window layer by SCAPS software. (20th June 2018) - He, Xu; Song, Yuehan; Wu, Lili; Li, Chunxiu; Zhang, Jingquan; Feng, Lianghuan
Abstract: Using a wider band-gap transparent conducting oxide (TCO) instead of CdS as the window layer of CdTe solar cells can increase the transmission of sunlight in the ultra-violet portion of the solar spectrum. In this paper, we tried to use Zn1- x Mg x O (ZMO) which is a ternary alloy with a controllable wide band gap as an alternative to CdS layer. The band structures of ZMO with different Mg compositions were calculated by using first-principles. Based on the theoretical calculation results, ZMO/CdTe solar cells were modeled and the device performances were simulated by using SCAPS software. The results show that the high conversion efficiency was obtained when the ZMO conduction band minimum exceeded that of CdTe layer by more than about 0.13 eV ( x  = 0.125). Furthermore, we focused on the effect of the thickness, donor density and interface states density of ZMO film ( x  = 0.125) on the performances of CdTe solar cells, and compared it with the simulation results of CdS/CdTe solar cell. For ZMO/CdTe solar cell, the primary contribution of the efficiency improvement was from the enhancement of the short-circuit current density, which resulted from the increase of the EQE at the wavelength less than 510 nm. The carrier recombination was increased for the high donor density and interface state density of ZMO film, which resulted in the low EQE at the short wavelength. Therefore, the efficiency of CdTe solar cell could be further improved up to 18.69% for the ZMO film with the appropriate donor density and the low interface state density of 10 14 cm −2 eV −1 .